Towards an HIV cure: science and debate from the International AIDS Society 2013 symposium. - Purcell, D; Elliott, J; Ross, A; Frater, J (2013)
The International AIDS Society convened the multi-stakeholder "Towards an HIV Cure" symposium in Kuala Lumpur, Malaysia in 2013 to address the significant research challenges posed by the search for a cure for HIV infection. Current antiretroviral regimens select for a small reservoir of cells that harbour latent HIV provirus, produce few or no HIV virions, and resist detection or clearance by host immunity. The symposium examined basic molecular science and animal model data, and emerging and ongoing clinical trial results to prioritise strategies and determine the viral and immune responses that could lead to HIV remission without ART. Here we review the presentations that scrutinized the molecular mechanisms controlling virus expression from proviral DNA, and the intrinsic cellular restriction and immune mechanisms preventing viral production. Insights from the basic science have translated into new therapeutic strategies seeking HIV remission without ongoing therapy, and much interest was focused on these ongoing trials. We also summarise the emerging ethical issues and patient expectations as concepts move into the clinic.